2014
DOI: 10.1039/c3py01005h
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and characterization of supramolecular elastomers based on linear carboxyl-terminated polydimethylsiloxane oligomers

Abstract: Supramolecular elastomers obtained through a two-step reaction of linear carboxyl-terminated polydimethylsiloxane oligomers (PDMS–COOH2) with diethylenetriamine (DETA) and urea show reasonable hysteresis and acceptable self-healing properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 24 publications
5
45
0
Order By: Relevance
“…Synthesis of ESESi. The ESESi elastomer was synthesized via a two-step process shown in Scheme 2, which is similar to the reaction in our previous work [28][29][30] and Leibler's report. 31,32 In the rst step, EPDMS x -COOH 2 (x ¼ 1/9, 1/11, or 1/15) and DETA were added at room temperature in a thermostated reactor tted with a Dean-Stark trap, a stirring system, and a nitrogen inlet, with a [-NH 2 ]/[-COOH] molar ratio of 2.2/1.…”
Section: Preparation Of Esesimentioning
confidence: 98%
“…Synthesis of ESESi. The ESESi elastomer was synthesized via a two-step process shown in Scheme 2, which is similar to the reaction in our previous work [28][29][30] and Leibler's report. 31,32 In the rst step, EPDMS x -COOH 2 (x ¼ 1/9, 1/11, or 1/15) and DETA were added at room temperature in a thermostated reactor tted with a Dean-Stark trap, a stirring system, and a nitrogen inlet, with a [-NH 2 ]/[-COOH] molar ratio of 2.2/1.…”
Section: Preparation Of Esesimentioning
confidence: 98%
“…19 An SESi was synthesized via a three-step synthesis process, as presented in Scheme 2; this was similar to the route reported by Leibler et al 16 Briefly, PDMS-COOH 2 reacted with UDETA in step 1 to introduce imidazolidone groups and were then reacted with DETA in step 2 to introduce secondary amines and increase the molecular weight. In step 3, 1,1-dialkyl urea was formed as a result of the reaction between amine and urea.…”
Section: Synthesis Proceduresmentioning
confidence: 99%
“…In our previous study, we found that with bifunctional carboxyl-terminated polydimethylsiloxane (PDMS-COOH 2 ), we successfully obtained SESis that exhibited rubberlike properties at room temperature. 18,19 Compared with the use of a mixture of mono-, di-, and tri-acids, the use of bifunctional linear oligomers is a more controllable synthesis route; it could help us to study the reaction mechanism and crosslinking structure in this system. We also studied the relationship between the mechanical, rheological, and self-healing properties of this material and the polydimethylsiloxane (PDMS) chain length in detail; this provided us with guidance for adjusting the properties of the SESis.…”
Section: Introductionmentioning
confidence: 99%
“…At room temperature, this material is noncrystallizable. In further research [45], Zhang studied the reaction mechanism of this system, which testified to the performance of the elastomers with different composition. The results showed that the rheological, mechanical, and self-healing properties can be adjusted by altering the PDMS chain length.…”
Section: 6mentioning
confidence: 99%